ANALISIS PEMBLOKIRAN LAYANAN INTERNET DI PAPUA DARI PERSPEKTIF ASAS KEPASTIAN HUKUM DAN ASAS KEPENTINGAN UMUM DEMI MEWUJUDKAN GOOD GOVERNANCE - Adam Prawira Abdi Kusuma; Raka Rayveda Yudhistira; Sesarius Noveno Dylan Kurniaputra (Jurnal Ilmiah Dinamika Hukum, 2023)
The issue of blocking internet services in Papua in 2019 has been in the public spotlight for quite a long time. The blocking carried out by the government raises questions about legal certainty, public interest in the principles of good governance. The principle of legal certainty is an important basis for the policy on blocking internet services in Papua, where this principle requires that the policies implemented must comply with applicable law, including clear procedures, predictability, and access to adequate information. In addition, service blocking must be based on a strong and transparent legal basis. The public interest must be an important consideration in blocking these internet services. The government must be able to maintain between individual interests and public interests. Even though the blocking has reasons such as national security or critical shelter, it still has to pay attention to the impact on individual human rights, freedom of speech and access to information. The realization of good governance is an important principle in the blocking. Good governance refers to good, transparent, accountable, participatory and fair governance. The government must involve the public in the process of making policies related to blocking internet services, such as accurate information, public consultation, and consider input from various related parties.